A Fracking Mess: Just Compensation for Regulatory Takings of Oil and Gas Property Rights - Lynch, Kevin J. (Columbia Journal of Environmental Law, 2019)
The law of takings receives much attention from courts and scholars. Yet much of that attention focuses on the questions of whether or not a taking has occurred, or whether the taking was for a public use. Less attention has focused on the appropriate measure of just compensation. This is understandable, because in many cases the requirement to pay just compensation would be too burdensome on the government, particularly in the more recent line of regulatory takings cases, and so if a taking is found, the government simply abandons its regulation and pays no or reduced compensation. Nevertheless, courts have attempted to grapple with the just compensation question and developed a variety of approaches that might be used to determine damages for takings on a case-by-case basis. Yet the lack of clear guidance from the courts and the potential for high damages awards due to the value of oil and gas likely means that government regulators are hesitant to step in to address the concerns of neighboring communities. Oftentimes, government officials operate on the misguided and incorrect assumption that mineral rights owners have an unqualified “right” to extract oil and gas, and this inhibits the creation or enforcement of rules that would interfere with fracking. Although the oil and gas industry has historically been lightly regulated, and therefore only a handful of takings claims related to oil and gas have ever been brought, that may change going forward. The technological developments that have enabled the latest fracking boom in oil and gas production in the United States have also dramatically increased the impacts that the industry has at the surface and on its neighbors. Thus, especially when oil and gas development occurs near residential areas, there is a growing demand for government regulation to address the worst of these impacts. These concerns are so great that some jurisdictions have gone so far as to ban fracking outright. As a result, the oil and gas industry and government regulators appear to be on a collision course that will only be resolved through takings litigation. Although no plausible takings claim related to recent regulations on fracking has yet been presented to the courts, it is entirely conceivable that such a claim might be brought in the future in New York or other jurisdictions that decide to ban the use of fracking to protect public health. For example, an owner of mineral rights in New York overlying the Marcellus or Utica Shale who has credible plans to extract oil and gas using fracking might be able to present a fracking-takings claim that could proceed to the merits. I have argued elsewhere that these restrictions on fracking should not be found to be a taking of private property. If courts reject these fracking-takings claims, then the compensation question is moot. However, if courts do find that regulation of fracking amounts to a taking, the question of how to measure just compensation presents numerous problems, as this Article will demonstrate. The main goal of this Article is to assess valuation of fracking-takings claims in light of the theory underpinning the Takings Clause, the nature of property interests in oil and gas, and the case law on regulatory takings. Scholars have advanced a number of theoretical approaches to justify various measures of just compensation and have identified key questions raised by the methods and by particular examples of takings. The most prominent reasons for requiring payment of just compensation are fairness and efficiency. However, both scholars and courts have paid limited attention to the unique problems that arise in attempting to determine just compensation for a taking of property interests in oil and gas—which I have previously defined as a fracking-takings claim. The vast majority of the literature deals with regulatory takings of real property interests, and most of that focuses on the question of whether a taking has occurred. For that portion of the literature addressing the measure of just compensation, the debate focuses on the best ways to determine just compensation for eminent domain or regulatory restrictions on developing property for residential or commercial use. Only a small handful of articles discuss the issue of whether regulation of fracking amounts to a taking, and none of them address in detail the question of how to value just compensation in those cases. This Article seeks to fill that gap in the literature by evaluating the match between existing takings law and fracking-takings claims—highlighting a number of difficulties that arise when calculating just compensation for oil and gas rights. Ultimately, existing valuation methods do not serve the underlying goals of fairness or efficiency, which calls into question the all-or-nothing approach to compensation under existing law. Specifically, theories requiring high compensation, when applied to the fracking-takings context, would break down by either unduly inhibiting appropriate government regulation or by shifting the enormous risk of fracking development from private entities to the public while creating windfalls for mineral interest owners at the public’s expense. Instead, low or context- dependent compensation theories are better suited to resolving fracking-takings claims because they can still allow for some compensation when fairness requires it, but they do not reward private property owners who have invested neither labor nor capital to increase the value of their oil and gas rights. Case law on this point is nearly as sparse as the literature. Only two cases have grappled seriously with the question of how to value a takings claim related to property rights in oil and gas, and in one of those the court ultimately concluded that no taking had occurred. This should not be surprising given the lack of significant public health restrictions on oil and gas extraction until recent times. Yet the expansion of regulation in many states with potential for oil and gas development means that governments may face takings challenges to their regulations going forward. Even the threat of potential takings litigation and liability can influence the decisions of governments who seek to balance concerns over fracking and its impacts on communities with the interests of mineral rights holders and oil and gas companies in pursuing the latest fracking boom. A careful evaluation of the thorny question of valuing a fracking- takings claim reveals numerous problems which undercut the goals of both fairness and efficiency. These problems derive from the characteristics of oil and gas as property. The right to extract oil and gas is different from ownership of oil and gas that has been extracted from the ground. Yet oil and gas in place is highly uncertain, both in the quantity recoverable, the cost to extract it, and the highly volatile market price at the uncertain time of sale. Additionally, in most cases the owner of oil and gas rights will have invested little to no money or labor in extraction of oil and gas when such extraction is prohibited by a ban on fracking. Thus, the question of just compensation for the takings of these property rights include the potential for private windfalls at public expense, the need to account for offsetting benefits of the broad regulation of oil and gas, and the shifting of the risk associated with fracking from private parties to the public. Each of these problems raises serious fairness concerns by enriching private property owners at the public’s expense. Additional problems of uncertainty, speculation, and gaming the system are present due to the high variability of the value of oil and gas reserves, which impair or perhaps utterly destroy the efficiency rationale. These problems in valuing fracking-takings can be reduced by moving beyond the all-or-nothing approach to just compensation that is implied by the existing regulatory takings doctrine. The all- or-nothing approach is reflected in the common statement that courts seek to put the property owner subject to a regulatory taking in the same position as if the property had not been taken. This is typically accomplished through calculating the fair market value of the taken property. However, this Article urges courts to move beyond fair market value. Rather than seeking to make the property owner whole as a result of a taking of property, courts should use a variety of valuation mechanisms to carefully calibrate just compensation awards to provide a fair amount of compensation without unduly inhibiting necessary regulation of oil and gas. Courts should therefore resist calls for high damage awards as just compensation for fracking-takings and instead allow government to exercise its traditional police power authority to decide whether, when, and how oil and gas may be extracted in a manner that is consistent with public health and safety.